Effects of addition of Sodium Benzoate of the Physicochemical Characteristic of Watermelon rind (Citrullus lanatus) - Imas Solihat; Septilina Melati Sirait (Politeknik AKA Bogor, 2021)
Watermelon rind is a food product that utilize wasted albedo waste. Generally, jam is gel or semi-dense so it has short shelf life. To make the jam more imperishable in storage, preservatives can be added in manufactured progress, one of the preservatives that can be used is sodium benzoate. This research aims to determine the effects of the addition of sodium benzoate on the physicochemical characteristics of watermelon rind jam. The results reveals that the formula of watermelon rind jam with the addition of sodium benzoate has physicochemical content that not much different apart from the one that isn’t added by sodium benzoate. The characteristics that were significantly different were only in viscosity, the jam with the addition of sodium benzoate (6400 cP) was greater than the jam without the addition of sodium benzoate (2900 cP). The selected formula will be tested by organoleptic (hedonic quality) with texture, taste, and aroma attributes with the results that the jam formula was well received by 30 panelists. The quality of watermelon rind jam is identified by color aspect with average score of 5.10 with good category that has brownish yellow color, by texture with average score of 5.10 with good category that has soft and fibrous textured, and by the taste with average score of 5,20 with good category that has sweet acidity taste. Keywords: Watermelon rinds, sensorics analysis